ANALISIS YURIDIS PEMENUHAN HAK SOSIAL EKONOMI MASYARAKAT MISKIN MELALUI ZAKAT DALAM PERSPEKTIF KEADILAN - Zainuddin Zainuddin (Arena Hukum, 2018)
Abstract The Zakat is a concept that refers to the redistribution of wealth determined by God to the category of the poor. In addition to poverty alleviation, zakat aims to eliminate greed among Moslems and encourage socially-oriented behavior. Islamic teachings affirm that zakat is the socio economic rights of the poor to be fulfilled whose main purpose is to uphold social and economic justice. In Indonesia, the management of zakat has undergone significant changes since the enactment of Act No. 23 year 2011 concerning Management of Zakat as a means to channel the socio-economic rights of the poor, the management of zakat is carried out as effectively as possible so that zakat funds can be transformed (changing mustahik into muzakki). Therefore, a modern and professional zakat management system is needed to achieve the main purpose of zakat namely poverty alleviation so that the social economic justice of the people is realized.AbstrakZakat adalah sebuah konsep yang mengacu pada redistribusi kekayaan yang ditentukan oleh Tuhan kepada kategori orang miskin. Selain pengentasan kemiskinan, zakat bertujuan untuk menghilangkan keserakahan di kalangan umat Islam dan mendorong perilaku yang berorientasi sosial. Ajaran Islam menegaskan zakat merupakan hak sosial ekonomi orang miskin yang harus dipenuhi yang tujuan utamanya untuk menegakkan keadilan sosial dan ekonomi. Di Indonesia, pengelolaan zakat telah mengalami perubahan signifikan sejak diberlakukannya Undang-Undang No. 23 Tahun 2011 tentang Pengelolaan Zakat sebagai sarana untuk menyalurkan hak-hak sosial ekonomi orang miskin, maka pengelolaan zakat dilakukan seefektif mungkin agar dana zakat dapat bertransformasi (mengubah mustahik menjadi muzakki). Oleh karena itu perlu sistem pengelolaan zakat yang modern dan profesional dalam mencapai tujuan utama zakat yaitu pengentasan kemiskinan sehingga terwujud keadilan sosial ekonomi umat.